Cassava torrado-like virus encodes a gene that facilitates the mechanical transmission to Nicotiana benthamiana of Cassava virus X (Scientia Agropecuaria, 2023)
Cassava-torrado-like virus (CsTLV) is a bipartite single-stranded RNA virus belonging to the family Secoviridae. The virus has been reported in Brazil and Colombia, and is usually found in mixed infections, and in plants affected by Cassava Frogskin Disease (CFSD), an endemic cassava disease in the Americas. Genome analysis of CsTLV identifies a gene in RNA2 implicated in pathogen movement in other torradoviruses. This gene (RNA2-ORF1) and another one no related to virus movement (Maf/Ham1) were amplified by PCR and cloned into constructs under the 35S promoter of cauliflower mosaic virus (CaMV), which then were transfered to agrobacterium binary vectors. When agro-infiltrated in Nicotiana benthamiana plants, only RNA2-ORF1 had a positive effect on the mechanical inoculation of cassava virus X (CsVX), a potexvirus that has a low rate of mechanical infection in N. benthamiana. Efficiency of CsVX mechanical transmission was measured by the number of infected plants, presence of symptoms, and titers of CsVX as measured by ELISA, two weeks after infection. On average, CsVX could infect 2.3 times more plants when these were previously agro-infiltrated with A. tumefaciens binary vector encoding CsTLV RNA2-ORF1. We conclude that the novel secovirid CsTLV associated with leaf spot symptoms in cassava, encodes a gene that could enhance other viral infections in N. benthamiana. Further studies are required to elucidate this effect and its role in mixed infections, often observed in cassava plants affected by CFSD.
Keywords: Cassava; mechanical transmission; secoviridae; virus interaction; virus movement